2023
DOI: 10.1002/hyp.15011
|View full text |Cite
|
Sign up to set email alerts
|

Lateral flow in bedrock dominates baseflow and flood flow in a catchment underlain with permeable sedimentary rock in the high‐relief Chichibu Mountains

Yuko Asano,
Masatoshi Kawasaki,
Kae Takatoku
et al.

Abstract: Determining the mechanisms of runoff generation is essential to land and water resource conservation, but lateral flow processes in high‐relief mountain areas remain unclear due to the difficulty to observe and measure these processes. This study demonstrates that lateral flow in bedrock dominates both high and low flows in a catchment underlain with permeable sedimentary bedrock in the high‐relief Chichibu Mountains. Through measurement of precipitation, discharge, soil, and stream temperatures and tracers (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
(110 reference statements)
0
0
0
Order By: Relevance
“…The phenomena observed at our sites may have been influenced by a relatively large contribution of bedrock groundwater discharge. Many observational studies have demonstrated the importance of bedrock groundwater discharge in various moderate‐ to high‐relief mountainous regions, small head hollows, hillslopes, and small catchments (e.g., Anderson et al, 1997; Uchida et al, 2003; Onda et al, 2006; Kosugi et al, 2006; Uchida & Asano, 2010; Padilla et al, 2015; Hale & McDonnell, 2017; Masaoka et al, 2021; Asano et al, 2023). Furthermore, Uchida et al (2008) and Asano and Uchida (2012) showed that catchments with small drainage areas have large inter‐basin differences in runoff processes, and the proportional contribution of bedrock groundwater discharge varies among slopes and catchments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomena observed at our sites may have been influenced by a relatively large contribution of bedrock groundwater discharge. Many observational studies have demonstrated the importance of bedrock groundwater discharge in various moderate‐ to high‐relief mountainous regions, small head hollows, hillslopes, and small catchments (e.g., Anderson et al, 1997; Uchida et al, 2003; Onda et al, 2006; Kosugi et al, 2006; Uchida & Asano, 2010; Padilla et al, 2015; Hale & McDonnell, 2017; Masaoka et al, 2021; Asano et al, 2023). Furthermore, Uchida et al (2008) and Asano and Uchida (2012) showed that catchments with small drainage areas have large inter‐basin differences in runoff processes, and the proportional contribution of bedrock groundwater discharge varies among slopes and catchments.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, empirically demonstrating the extent of groundwater contributions and elucidating the conditions and hydrological mechanisms occurring at these smaller sites are important research topics. In particular, it is valuable to quantify in greater detail the groundwater dynamics and their contributions to water discharge depending on rainfall magnitude in a high-relief sedimentary rock mountain area such as our site, with very limited observational data, using tracers, flow analysis, and ground and water temperature, as discussed by Asano et al (2023).…”
Section: Effect Of Bedrock Groundwater Discharge On Peak Lag Timementioning
confidence: 99%